Use of oral contraceptives to manipulate menstruation in young, physically active women - Schaumberg, M. A.; Emmerton, L. M.; Jenkins, D. G.; Burton, N. W.; Janse de Jonge, X. A. K.; Skinner, T. L. (International Journal of Sports Physiology and Performance, 2018)
Purpose: Menstruation and menstrual symptoms are commonly cited barriers to physical activity in women. The delay or avoidance of menstruation through extended oral-contraceptive (OC) regimens may mitigate these barriers, yet information on menstrual-manipulation practices in young physically active women is sparse. The objective of this study was to investigate prevalence of, and reasons for, menstrual manipulation with OCs in recreationally and competitively active women. Methods: One hundred ninety-one recreationally active (self-reported moderate to vigorous physical activity 150-300 min/wk) women (age 23±5 y), 160 subelite recreationally active (self-reported moderate to vigorous physical activity >300 min/wk) women (age 23 ± 5 y), and 108 competitive (state-, national- or international-level) female athletes (age 23?±?4 y) completed a self-administered questionnaire assessing OC-regimen habits and reasons for manipulation of menstruation. Results: The majority (74%) of OC users reported having deliberately manipulated menstruation at least once during the previous year, with 29% reporting having done so at least 4 times. Prevalence of menstrual manipulation (at least once in the previous year) was not different between competitive athletes, subelite recreationally active women, and recreationally active women (77% vs 74% vs 72%; P>.05). The most cited reasons for manipulating menstruation were special events or holidays (rated by 75% as important/very important), convenience (54%), and sport competition (54%). Conclusions: Menstrual manipulation through extended OC regimens is common practice in recreationally and competitively active young women, for a range of reasons relating to convenience that are not limited to physical activity. This strategy may help reduce hormone-related barriers to exercise participation, thereby positively affecting participation and performance.